Sistem Pakar Diagnosis Penyakit Kulit Pada Kucing Menggunakan Metode Certainty Factor - Palguna, David; Jusak, Jusak; Sutomo, Erwin (Jurnal JSIKA, 2014)
Skin disease is a type of diseases that frequently infects pets especially cat. Cat that is infected the skin diseases, may initially looked fine. Based on interview with veterinarian who specializes in dogs and cats diseases, skin evaluation to the pets are considered to be very important. In some cases where skin diseases are not handled properly, it result in severe illness to the pets. Mostly veterinaries open up their practice only in big cities. Therefore most of the time, the cat owners are lazy to give proper treatment against the skin diseases that are suffered by their cats. Based on the problem above, it is neccessary to build an expert system that is able to support clinic and cat owners to diagnose the skin diseases of their pets. The certainty factor expert system will be used to detect every symptom that is suffered by cats. The new system will generate diagnosis of skin diseases for cats. The experiment results of this expert system indicate that the system is able to identify 91.6% accuracy of the type skin diseases. The result is obtained by the examination of 12 cats that suffer skin diseases in Moii Pet Care veterinary clinic.